Opportunities, gaps, and challenges in the implementation of the One Health approach in Kenya - Bukachi, Salome R.A.; Onono, Joshua O.; Onyango-Ouma, Washington; Onyango, Tonny; Jeptoo, Mosbei; Yussuf, Buke; Knight-Jones, Theodore J.D.; Fèvre, Eric M.; Richards, Shauna (CAB International, 2024)
The health of humans, animals, and the environment are all under unprecedented, interdependent risks. The Quadripartite Organizations (FAO, UNEP, WHO and WOAH) define OH as an integrated, unifying strategy that seeks to optimally and sustainably balance the health of people, animals, and ecosystems. Capacitating One Health in Eastern and Southern Africa (COHESA) is a project with the objective of facilitating the rapid uptake, adaptation, and adoption of solutions using the OH concept embedded across government and research entities, educational and training institutes, and public-private partnerships in Eastern and Southern Africa. The COHESA project team in Kenya conducted a baseline assessment to understand challenges, gaps, and capacities in OH in the country. The findings illustrated that an OH strategic plan for the period 2021 to 2025 was launched in Kenya and had three strategic objectives: (a) to strengthen implementation of the OH approach at national and county levels, (b) to strengthen prevention, surveillance, response, and control of priority zoonotic diseases in both humans and animals, (c) to conduct applied research using OH approach. The findings also illustrated that the country has been involved in several activities involving a multisectoral OH approach, including but not limited to research and innovation, national policies and strategies development, capacity building of human and animal health workforce, and implementation. Despite making these steps, challenges persist in translating policies into effective actions, and limited collaboration among actors while public awareness and involvement of the environmental sector remain suboptimal.